2017
DOI: 10.1021/acsami.6b13410
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Organic-Cation (FA)x(MA)1–xPbI3 Planar Perovskite Solar Cells with 16.48% Efficiency via a Low-Pressure Vapor-Assisted Solution Process

Abstract: Compared to that of methylammonium lead iodide perovskite (MAPbI), formamidinium lead iodide perovskite (FAPbI) has a smaller energy band gap and greater potential efficiency. To prevent the transformation of α-FAPbI to δ-FAPbI, preparation of (FA)(MA)PbI was regarded as an effective route. Usually, the planar (FA)(MA)PbI perovskite solar cells are fabricated by a solution process. Herein, we report a low-pressure vapor-assisted solution process (LP-VASP) for the growth of (FA)(MA)PbI perovskite solar cells th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 53 publications
5
91
0
Order By: Relevance
“…[47] This strategy has been explored both in single crystals [47] and thin films. [7,10] Ambient stabilization of the desirable α-phase has been demonstrated for both partial substitutions with MA [24,34,42,163] and Cs. [57,125] It was also reported that the stable cubic phase is obtained in FA x MA 1−x PbI 3 for 0.2 ≤ x ≤ 0.9, while the tetragonal phase is obtained for low values of x (high MA content).…”
Section: Mixed Composition Perovskitesmentioning
confidence: 99%
See 3 more Smart Citations
“…[47] This strategy has been explored both in single crystals [47] and thin films. [7,10] Ambient stabilization of the desirable α-phase has been demonstrated for both partial substitutions with MA [24,34,42,163] and Cs. [57,125] It was also reported that the stable cubic phase is obtained in FA x MA 1−x PbI 3 for 0.2 ≤ x ≤ 0.9, while the tetragonal phase is obtained for low values of x (high MA content).…”
Section: Mixed Composition Perovskitesmentioning
confidence: 99%
“…[134] It should also be noted that a significant improvement (three times longer carrier lifetime) was reported for FA x MA 1−x PbI 3 compared with FAPbI 3 . [163] Furthermore, the carrier lifetime in mixed perovskite FA x MA 1−x PbI 3−3x Br 3x single crystals was found to be more than 20 times longer compared with that in FAPbI 3 single crystals. [41] Thus, mixed-composition perovskites can provide a potential advantage, not only in terms of phase stabilization but also in terms of improved charge transport.…”
Section: Long Diffusion Length and Low Charge Recombinationmentioning
confidence: 99%
See 2 more Smart Citations
“…It begins with deposition of a metal halide, such as crystalline PbI 2 , which is subsequently exposed to the cation salt and thermally converted into the perovskite phase. This process has been studied and optimized extensively for MAPbI 3 and promises similar high‐quality FAPbI 3 films, but has yielded much lower PCE, given the higher energy of formation of FAPbI 3 compared to MAPbI 3 , as well as the formation of nonperovskite intermediates . Incorporating Cs + in the two‐step approach would be useful to promote conversion like in the one‐step process, but it is quite challenging because of the low solubility of CsI in isopropanol (IPA) solvent used for deposition of methylammonium halide salts .…”
Section: Introductionmentioning
confidence: 99%